173k views
2 votes
Write the quadratic equation y= (x)2-6x-7 in vertex form

User Aularon
by
5.7k points

2 Answers

3 votes

Answer:y = (x-3)^2 -16

Explanation:

User Tnunamak
by
6.1k points
0 votes

Answer:

y = (x-3)^2 -16

Explanation:

y = x^2 -6x-7

We need to complete the square

b= -6

b/2 = -6/2 = -3

(b/2) ^2 = (-3)^2 =9

Add 9 then subtract 9 to balance the equation

y = x^2 -6x +9 -9 -7

y = (x^2 -6x+9) -16

The terms in parentheses is (x-b/2)^2

y = (x-3)^2 -16

This is in vertex form

The vertex is (3,-16)

User Jpoveda
by
7.1k points